Deposition behavior, microstructure and mechanical properties of an in-situ micro-forging assisted cold spray enabled additively manufactured Inconel 718 alloy - Luo, Xiao-Tao; Yao, Meng-Lin; Ma, Ninshu; Takahashi, Makoto; Li, Chang-Jiu (Materials & design, 2018)
Cold spray is capable to additively manufacture oxide-free metallic parts in open air due to its low processing temperature. However, for metals with relatively high hardness such as Inconel 718 superalloy (IN718), it is still a big challenge to get dense deposits by using low-priced nitrogen gas. In this work, In-situ micro-forging (MF) was introduced to cold spray by mechanically mixing big-sized 410 stainless steel (410SS) particles into the IN718 powder so that the deposited IN718 layer can be hammered and plastically deformed by the MF particles during spraying and results in fully dense deposits. As 50 vol% MF particles were mixed into the IN718 powder, the porosity was decreased from 5.6% to 0.26%. Due to the low impact velocity, 410SS particles were not embedded into the IN718 deposits and the possible contamination was avoided. An oxide scale removal induced increment in deposition efficiency was detected for the first time. Due to the lower porosity and enhanced inter-particle bonding, a great improvement in ultimate strength from 96 to 464 MPa was achieved by the in-situ MF effect. After heat treated at 1200 °C for 6 h, the sample fractured at a high strength of 1089 MPa and revealed a ductile fracture manner. [Display omitted] •In-situ micro-forging was introduced to cold spray by a facile approach.•Fully dense IN718 deposit was achieved without any contamination.•Increased deposition efficiency induced by oxide scale removal was first detected.•Ultimate strength increases from 96 to 464 MPa due to the micro-forging effect.•Effect of heat treatment on microstructure and tensile behavior was studied.